MENGKRITISI MODEL KONSELING BERBASIS BUDAYA NUSANTARA: MODEL KIPAS - Zulfikar Zulfikar; Zubaidah Zubaidah (IAIN Batusangkar, 2020)
The presence of the KIPAS model is an effort to strengthen the dignity of Indonesian counselors and counselors who have been oriented towards western culture. Western culture which is clearly incompatible with our culture, Nusantara culture which adheres to eastern culture. The attraction of the BK Model KIPAS is the use of cultural values as the basis for implementing BK services, thus giving rise to an enlightenment in the implementation of BK services in the archipelago. This gives an enthusiasm and hope that the idea of a counseling model based on this archipelago culture will be accepted now and especially in the future. The model is an acronym for KIPAS, which is intensive and progressive counseling that is adaptive to structure. The existence of the KIPAS model will be able to answer problems that occur such as the many unresolved student problems and improvements to the image of BK in society. So far, we have seen that the implementation of counseling guidance services in schools in Indonesia has become something students dislike. As a new model in the world of BK, of course it cannot be separated from the strengths or strengths and weaknesses or weaknesses of the KIPAS model itself. The KIPAS model should accommodate all cultures in Indonesia from Sabang to Merauke.